Evaluation of the Harmony soundprocessor in combination with the speech coding strategy HiRes 120 - Brendel, Martina; Buechner, Andreas; Krueger, Beate; Frohne-Buechner, Carolin; Lenarz, Thomas (Otology & neurotology, 2008)
The Advanced Bionics Harmony BTE processor was developed to support the new speech coding strategy HiRes 120 with a resolution of 120 channels based on "current steering." Compared with the previous Auria, the front end has been re-designed and power consumption reduced. HiRes 120 as well as the impact of the improved Harmony processing concerning a better speech understanding were evaluated. Subject's performance was evaluated using a test battery of the Hochmair-Schulz-Moser (HSM) sentence test and questionnaires regarding general sound quality, music perception, battery life time and processor handling. In the first study group, 11 postlingually deafened adult subjects participated with a minimum of 9 months experience. The second study group consisted of 14 postlingually deafened adult subjects with a minimum of 2 years experience. Tested were the 2 speech coding strategies HiRes and HiRes 120 on the Harmony and the clinical system, respectively. Speech perception tests in quiet, in CCITT noise, as well as with a competing talker, questionnaires regarding sound quality and handling and perceptual channel tests. A total of 84% showed a clear preference for the Harmony processor compared with their previous processor with HiRes. The speech test results showed a 7.7% average increase in the HSM sentence test with 5 dB SNR competing talker. The majority of the subjects wanted to change to the new Harmony processor because of a better understanding in everyday life, handling, and improved battery-life time.